The role of ecological processes in structuring reef fish communities in the Agulhas Ecoregion, South Africa - Dyer, Alexander (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2018)
Local, niche-based processes, which arise from the interplay between biotic interactions and abiotic constraints are considered to be important regulators of community structure. However, it is increasingly recognised that patterns of diversity can also be strongly influenced by dispersal-driven processes. While empirical research on the diversity of coral reef fishes on shallow tropical reefs has contributed greatly to the development of general concepts in ecology, there have been considerably fewer studies on the processes which shape the diversity of fish communities on shallow (10 - 30 m) and deep (30 - 75 m) rocky reefs. Consequently, it is less clear at which spatial scales niche partitioning and dispersal limitation contribute most strongly to the structure of reef-associated fish communities within rocky reef ecosystems. To address this caveat, research was conducted at four rocky reef complexes within the warm-temperate Agulhas Ecoregion, South Africa. The diversity of reef-associated fishes was sampled by baited remote underwater stereo-video systems (stereo-BRUVs) to incorporate the range of heterogeneous reef habitat in Tsitsikamma National Park Marine Protected Area (TNP MPA) and Algoa Bay (AB). To examine how niche-based and dispersal-driven processes influence patterns of diversity among species within the dominant family of resident fishes, the sparids (Sparidae), components of diversity were quantified at several spatial scales. Turnover in the number of species which locally co-occurred was found to be largely driven by the limited dispersal of species over hundreds of kilometres. When relative species abundances were taken into account, sparid communities were characterised by higher than expected rates of compositional turnover among local habitat patches separated by hundreds to thousands of metres of contiguous reef. Patterns of compositional turnover were associated with the spatial aggregation of conspecifics, particularly at scales which facilitate the post-settlement dispersal of fishes. Niche-based segregation of species along the depth gradient was found to be the primary driver of compositional turnover among both protected and exploited communities. However, spatial structuring within reefs, which was independent of variation in the environment, suggests that compositional differences among communities are also influenced by the limited post-settlement dispersal of resident fishes to adjacent areas during their ontogeny. Together, the results suggest that the diversity of reef-associated sparids is likely to depend both on an adequate diversity of suitable reef habitat and a sufficient degree of spatial connectivity to facilitate ontogenetic habitat shifts. Taxon-based descriptors of diversity do not adequately account for ecological difference among conspecifics within size-structured populations. To test whether differences in body size facilitated coexistence among sparid fishes, the number of species which coexisted at the local scale was related to variation in the size structure of communities. In communities which have been historically protected from fishing, local coexistence between a greater number of species was promoted by reduced levels of intraspecific variation in size of fishes. This suggests that, among species with similar trophic requirements, further niche segregation along a prey-size and body-size gradient is likely to mitigate the direct impacts of competition for shared food resources. Among exploited communities, size structure did not influence the number of species which coexisted at the local scale. This finding suggests that fishing-induced mortality of larger-bodied fishes is likely to remove some of the constraints to colonisation which arise from asymmetries in competitive fitness between small and large-bodied fishes. Together, these results highlight the importance of post-settlement processes and population size structure to the maintenance of reef-associated fish diversity within contiguous rocky reef habitats.
Keywords: Reef fishes -- South Africa -- Agulhas, Cape (Cape); Reef fishes -- Ecology -- South Africa -- Agulhas, Cape (Cape); Marine biodiversity -- South Africa -- Agulhas, Cape (Cape); Biotic communities -- South Africa -- Agulhas, Cape (Cape); Sparidae -- South Africa -- Agulhas, Cape (Cape); Reef fishes -- Size -- South Africa -- Agulhas, Cape (Cape); Baited remote underwater stereo-video systems (stereo-BRUVs)